Effect of Phenological Variation on the Phytochemical Composition and Antioxidant Activity of Different Organs of Capparis spinosa L. - Saeid Hazrati; Zahra Mousavi; Saeed Mollaei; Hossein Rabbi Angourani; Silvana Nicola (Horticulturae)
Capparis spinosa L. (caper) is an important medicinal plant whose bioactive compounds vary significantly depending on its growth stage. This directly affects its pharmaceutical and nutritional value. Collecting C. spinosa at the optimal growth stage is essential to achieving high phytochemical quality and meeting consumer needs. This study aimed to evaluate the variation of these active compounds in the aerial parts of C. spinosa across four phenological stages (vegetative, flowering, unripe fruit, and ripe fruit). The result showed that EO content was highest in unripe fruits (0.18%) and lowest in the flowering stage (0.07%) in leaves, while extract yield was highest in leaves of the ripe fruit stage (14.65%) followed by the flowering stage in flowers (12.66%). Flowering stage leaves showed the highest total phenol (56.20 mg GAE/g) and flavonoid (17.10 mg QE/g) content, while the lowest concentrations were found in the ripe fruit stage of the leaves. EO analysis showed that methyl isothiocyanate reached the highest concentration in flowers at the flowering stage (41.6%), while isopropyl isothiocyanate reached the highest concentration in leaves at the ripe fruit stage (36.2%). Isobutyl isothiocyanate was found exclusively in fruits, with the highest concentration in ripe fruits (9.2%). Dimethyltrisulphide showed a maximum concentration in leaves at the vegetative stage, decreasing by 76.6% as the plant developed towards the ripe fruit stage. The dominant phenolic acids varied between phenological stages: cinnamic acid at the vegetative stage; rosmarinic and cinnamic acids at the flowering stage in leaves; caffeic and cinnamic acids in flowers; vanillic, cinnamic, and rosmarinic acids at the unripe fruit stage in leaves and fruits; and rosmarinic, cinnamic, and vanillic acids in ripe fruits. The results indicate that harvesting C. spinosa at the vegetative stage and in the leaves of the flowering stage is optimal for maximum secondary metabolite yield, providing valuable guidance for growers targeting food and pharmaceutical applications.